ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI PORTABLE FAN THERAPY TERHADAP DISPNEA PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIS (PPOK) DI IGD RS BHAYANGKARA TK.I R. SAID SUKANTO - Muhamad Alfian (2022)
Chronic Obstructive Pulmonary Disease (COPD) is a lung disease characterized by chronic obstruction of airflow in the lungs that interferes with normal breathing which can be life-threatening. COPD is the third leading cause of death in the world and accounts for 6% of the 55.4 million deaths worldwide. One of the symptoms felt in patients with COPD is dyspnea. One of the most frequently used pharmacological treatments to treat dyspnea is the administration of bronchodilators. Bronchodilators work by decreasing dynamic hyperventilation at rest and activity, and improving tolerance to activity. The purpose of providing this innovative intervention is to determine whether portable fan therapy can have an effect in reducing dyspnea in patients with chronic obstructive pulmonary disease (COPD) at the ER Bhayangkara Tk.I R. Said Sukanto Hospital. The instrument for measuring the dyspnea scale used in evaluating the provision of this innovative intervention is the Modified Borg Scale (MBS). The final result obtained in the provision of this innovative intervention was that the dyspnea scale in COPD patients decreased by approximately 1 point after administering portable fan therapy to the facial area for 5-6 minutes. Based on these results, it can be concluded that the use of portable fan therapy can reduce the dyspnea scale in patients with COPD.